Arduino-Uno Based Mobile Data Logger with GPS Feature - Muhammad Abu Bakar Sidik; Mohd Qamarul Arifin Rusli; Zuraimy Adzis; Zolkafle Buntat; Yanuar Zulardiansyah Arief; Hamizah Shahroom; Zainuddin Nawawi; Muhammad ‘Irfan Jambak (Universitas Ahmad Dahlan, 2015)
Lightning activity correlates with the formation of thunderclouds which increase the atmospheric electric field (AEF) between the cloud and the earth. Observations of the development of the AEF will allow the prediction of lightning activities close to a particular location. In research and development, the data logger plays an important role to observe and collect data from AEF sensors. The data logger must be reliable and effective. High investment costs are involved in acquiring a data logger, and choosing a suitable data logger is not easy. Institut Voltan dan Arus Tinggi (IVAT) is develeloping AEF sensor. Along with that sensor development a data logger development is also required. In this paper, a mobile data logger is developed by using Arduino-Uno. This mobile data logger is equipped with a GPS module, which provides accurate positioning in the collection of data. Laboratory and field tests were carried out to observe the performance of the mobile data logger system. The results showed that the developed data logger works properly.